Active, Healthy, Productive, and Independent Elderly People in Nursing Homes Bethania BNKP - Idarni Harefa; Nurhayati Zega; Berkat Perlindungan Zamasi; Andri Krisman Zebua; Binsar Jun Imer Zega; Dede Kurniawan Zega; Febri Liani Putri Lase; Happy Notatema Zai; Nefirman Bate'e; Sofyan Fran Wijaya Telaumbanua (Communautaire: Journal of Community Service, 2025)
The Community Service Program (PKM) implemented at Bethania Nursing Home aims to create active, healthy, productive, and independent seniors for as long as possible. One effort to empower the elderly is through the formation and development of Elderly Groups, namely Posyandu Lansia or Posbindu Lansia. Through these groups, seniors are encouraged to remain active and motivated in maintaining a healthy lifestyle by participating in elderly exercise and undertaking to live a healthy, active, and productive life. This outreach activity involved 15 elderly residents of Bethania Nursing Home and was carried out over one day using media such as projectors, banners, loudspeakers, and laptops. Evaluation was carried out by observers using a checklist that assessed the process and results of the outreach. The evaluation results showed that all seniors understood the material, actively participated, and were committed to regularly doing elderly exercise and living a productive and healthy daily life.